Chromatin accessibility regulates age-dependent nuclear mechanotransduction - Yawen Liao; Luezhen Yuan; Trinadha Rao Sornapudi; Max Land; Rajshikhar Gupta; G. V. Shivashankar (Proceedings of the National Academy of Sciences, 2026)
The integration of environmental cues into cellular programs is crucial for cell function. Yet, how this integration is modulated due to cellular aging remains unclear. We propose that the 3D chromatin organization filters these signals and investigated how age-related chromatin changes in human dermal fibroblasts affect responses to mechanical tension and TGF-β. Young fibroblasts exhibited synergistic gene expression enhancement in response to combined stimuli, a response that was markedly blunted or divergent in aged cells. These distinct outcomes correlated with significant age-related differences in chromatin accessibility. We identified the AP-1 complex and other transcription factors with age-specific activity as pivotal in remodeling chromatin and orchestrating these divergent mechanochemical responses during cellular aging. We validated that disrupting AP-1 activity inhibits fibroblast activation by preventing JUNB recruitment to the transcription machinery. Our findings establish chromatin as a key integrator of mechanochemical signals and characterize the age-related alterations to this integration that modify the cellular responsiveness of aged cells, highlighting AP-1 and its network as potential therapeutic targets against age-related decline.